ANALISIS KARAKTER PROTAGONIS DALAM FILM “PERFUME: THE STORY OF A MURDERER” - Hakim, Agus; M. Firdaus Benyamin; Budiman, Budiman (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
This article contains the results of the analysis of the protagonist's character in the film "Perfume: The Story of a Murderer." The purpose of this writing is to describe the results of the analysis of the protagonist's character, which is not a human but a perfume that plays the role of the protagonist. This research was conducted using a qualitative research method with a descriptive approach that will result in descriptive data based on theoretical foundations using Sigmund Freud's psychoanalytic theory. The result of this research is an analysis of the protagonist's character in the film "Perfume: The Story of a Murderer," which is not a human but a perfume. Observing this phenomenon can be used as a reference to convey that the main character in the film is not a human but an object in the form of perfume.